Potential conflicts of interest in Indonesia's energy transition policy - Firdaus Cahyadi; Soeryo Adiwibowo; Edy Hartulistyoso (Privietlab, 2025)
Energy is of paramount importance to public interest, as underscored by the Indonesian Constitution, which mandates state intervention to safeguard these interests. Nevertheless, Indonesia’s energy policy is frequently dominated by specific actors, potentially leading to conflicts of interest that may adversely affect the public. This study reveals that both fossil-based and renewable energy policies are consistently influenced by elites from international financial institutions and national actors with close affiliations with political elites. This research identifies international funding bodies, such as the World Bank and the Asian Development Bank (ADB), as the predominant actors in Indonesia's energy transition policy. In addition to international elites, national elites also exert a significant influence on energy transition policies. Consequently, active participation in the civil society is essential. The predominance of a single actor in the formulation of energy policies can result in inequitable energy policies.